Analisis Manajemen Strategik - Azmi, Ulul; Yadi, Sumrah; Zubairi, Zubairi; Maftuhah, Maftuhah; Zahruddin, Zahruddin (Universitas Islam Negeri Walisongo, 2023)
Strategic management is the science and art of planning, implementing, evaluating every decision of organization that can enable performance to meet targets and get goals. This research aims to describe strategic management which includes planning, implementation and evaluation of strategies at SDIT Citra Az-Zahra West Jakarta. The research approach and methods use descriptive qualitative using data collection through literature studies, documentation, documentation. Data analysis are carried out by collect of data, reduce of data, present of data, and draw of conclusions. Meanwhile, data validity use data and method and source triangulation. The results of research strategic management research at SDIT Citra Az-Zahra include several activities, namely planning including formulating vision, mission and goals, identifying internal and external factors, determining superior strategies, short until long-term planning. Strategic implementation is determining school policies which include government policies and the school's own policies, motivating educators and education staff by providing several awards, human resources allocated, and school culture. Strategic evaluation includes monitoring of plan and implementation, individual and school performance measured, and improvement steps taked.